Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Synthesis and valorization of corn silk-derived carbon dots for antimicrobial fruit preservation - Yong-Ping Wen; Meng-Ting Wu; Kwang-Pyo Kim; Meng-Yi Chen; Jia-Hui Liu; Ya-Ping Li; An-Guo Wu; Xiang Li; Song-Zhi Xie; Die Gao; Jian-Ming Wu; Xiao-Gang Zhou (International Journal of Food Microbiology, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Highly efficient discovery of CYP1B1 inhibitors from licorice as novel anti-fibrotic agents via integrating interdisciplinary methodologies - Ziwei Li; Yumeng Hao; Ya Yang; Jingxuan Lei; Feng Zhang; Yunqing Song; Hao Yin; Ziru Dai; Shenglan Qi; Yongbin Cao; Guangbo Ge (Toxicology and Applied Pharmacology, 2026)

Concentration-dependent variation in carbon allocation and microbial assembly in chain elongation microbiota: Comparative effects of acetate, ethanol, and lactate - Ya-Ning Song; Li-Juan Chai; Ling Ao; Jun-Lan Mei; Yu-Long Li; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Bioresource Technology, 2026)

Modeling and analysis of structural effects and detection characteristics for a new toroidal coil–excited lateral resistivity logging-while-drilling (LWD) tool - Ya-Ping Zheng; Wei Xu; Hao Li; Yong-Song Zheng; Wei-Ping Wu; Ze-Hua Yan; Xin Li; Min Liu (Applied Geophysics, 2026)

Creation of water management systems and social sustainability: exploring millennial human–spring relationships in semi-arid North China - Teligeer Bao; Adrian D. Werner; John Schofield; Yongze Song; Geng Li; Ziyue Zhu; Yonghong Hao; Long Xing; Ya Zhou; Wenjing Liu; Yu-Li Wang (Hydrological Sciences Journal, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Magnetotelluric strong interference detection and signal reconstruction via recurrence quantification analysis and deep learning - Pei-Lin Zhang; Jia-Qing Wang; Jian-Nan Song; Run-Lin Luo; Ya-Nan Li; Chang-Wei Li (Applied Geophysics, 2026)

Dopamine-coated LTO particles immobilized in PVA with directional dendritic channels for fast and selective lithium capture from salt-lake brines - Xunshuang Zhang; Yiming Hua; Mengyu Xie; Yihan Guo; Shilei Zhu; Yu He; Junxiang Wu; Shusen Chen; Zhou Song; Ya Nan Ye; Liangbin Li (Desalination, 2026)

Macroporous polyamidoxime particles with tunable cyclization functionalization via a swelling-restricted pore-locking preservation strategy for efficient uranium extraction from seawater - Junxiang Wu; Yu He; Xunshuang Zhang; Hongguang Mo; Yi Nan Wang; Shusen Chen; Zhou Song; Ya Nan Ye; Liangbin Li (Chemical Engineering Journal, 2026)

Structural characterization and in vitro evaluation of the hypolipidemic activity of the HSP-Ia, a bioactive polysaccharide derived from hemp (Cannabis sativa L.) seeds - Ya-Zhi Wang; Lan-Yan Li; Yong-Zhe Chen; Dong-Xue Song; Feng-Yu Liu; Zi-Yi Zhang; Hong-Lin Guo; Jun Li; Tao Liu; Chen-Feng Ji; Shou-Dong Guo (Carbohydrate Polymers, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Unraveling the molecular evolution and immune functions of Lr-CD40 in Lethenteron reissneri - Liang Zhao; Zihao Yan; Mingwei Du; Xiaoping Song; Xianhui Li; Ya Pang; Ding Li; Guoxiu Ma; Yuetong Zhao; Feng Sun; Yinglun Han (Fish Physiology and Biochemistry, 2026)

Two new five-membered heterocyclic compounds isolated from Polygonum tinctorium - Pei-yuan Yang; Wei-qi Zhang; Ya-jie Yuan; Li-li Lou; Xiao-xiao Huang; Shao-jiang Song (Natural Product Research, 2026)

Comprehensive Analysis of Cyan Soft-Carapace and Red Hard-Carapace Color Variants in Procambarus clarkii: Muscle Quality, Carapace Pigmentation, and Tissue-Specific DGAT2 mRNA Expression - Silei Xia; Yunqing Liu; Jingyi Zhang; Ya Dong; Xiao Yuan; Kunyuan Hu; Shiping Yang; Zhuozhuo Ai; Mingyou Li; Guangtong Song; Hongyan Tian; Wuxiao Zhang; et al. (Fishes, 2026)
Crayfish with cyan soft-carapace and red hard-carapace differ considerably in market value. To investigate the causes underlying this difference in shell color, we selected 120 healthy Procambarus clarkii of similar size (9–10 cm), equally divided by shell color and sex. Muscle quality, pigment deposition, and DGAT2 mRNA expression were compared between the two shell-color types. The results showed that: (1) Muscle hardness was significantly higher in red hard-carapace crayfish than in cyan soft-carapace crayfish (p 0.05). (2) A significant interaction between shell color and sex influenced crude fat and ash content (p 0.05), with no notable differences across groups. (4) The contents of astaxanthin, lutein, and β-carotene in the shell were significantly influenced by the interaction between sex and shell color (p

First record of Fraxinoxylon (Oleaceae) from the Miocene of Sihong, Jiangsu Province, China, and its palaeogeographic implication - Yanbin Zhu; Ya Li; Xiaohua Zhou; Yanfeng Song; Kai Liu; Ren Jiang; Yeming Cheng (Review of Palaeobotany and Palynology, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

First report of scale drop disease virus (SDDV) infection in cultured silver pomfret (Pampus argenteus) in China: Isolation and pathogenic characterization - Su-Ming Zhou; Yang-Yang Bai; Deng-Feng Li; Jia-Song Xie; Ya-Jun Wang; Fei Yin (Aquaculture, 2026)

Ectoine modulates mixotrophic denitrification pathway partitioning to sustain stable nitrogen and phenol removal under hypersaline stress - Jingwen Song; Ya-Nan Hou; Ran Li; Zengyue Feng; Ai-Jie Wang; Nanqi Ren; Wei Wei; Bing-Jie Ni; Cong Huang (Water Research, 2026)

Freeze-casting polyamidoxime-based membrane adsorbents with synergistically enhanced mechanical properties and adsorption performance for uranium extraction from seawater - Yu He; Yanran Lu; Beibei Kang; Junxiang Wu; Xunshuang Zhang; Shilei Zhu; Zizhou Xu; Shusen Chen; Zhou Song; Ya Nan Ye; Liangbin Li (Journal of Environmental Chemical Engineering, 2026)

Morpho-molecular taxonomy and systematics of Suctoria (Ciliophora, Phyllopharyngea), with descriptions of four species from wetland habitats in China - Mingzhen Ma; Yiwen Wang; Wen Song; Honggang Ma; Ya Wang; Khaled A.S. Al-Rasheid; Weibo Song; Alan Warren; Zhe Wang; Lifang Li; Xiangrui Chen (European Journal of Protistology, 2026)

Environmental heat and cold stress, thyrotropin abnormalities, and reduced fecundability in 14 million Chinese couples: A nationwide preconception cohort study - Xinghou He; Mengyao Li; Ying Yang; Xinyi Lv; Hongbing Xu; Bin Zhang; Long Wang; Chuanyu Zhao; Jiahui Liu; Yuan He; Jianbing Wu; Xinghua He; et al. (Environmental Research, 2026)

In-situ radical polymerization for solid polymer electrolytes in lithium-ion batteries: a comprehensive review - Yong Luo; Churu Zhang; Ya Liao; Zhitian Ding; Defu Li; Lufa Zhu; Hao Luo; Beiyuan Liu; Jiali Guo; Xiaoli Peng; Shipai Song; Yong Xiang; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Caffeic acid-grafted chitosan/sodium alginate/nanoclay-based multifunctional 3D-printed hybrid scaffolds for local drug release therapy after breast cancer surgery” [Carbohydrate Polymers 324 (2024) 121441] - Ya Su; Yaqian Liu; Xueyan Hu; Yueqi Lu; Jinyuan Zhang; Wenbo Jin; Wang Liu; Yan Shu; Yuen Yee Cheng; Wenfang Li; Yi Nie; Bo Pan; et al. (Carbohydrate Polymers, 2026)

Hematopoiesis could be improved by correcting aberrant bone marrow macrophages polarization in aplastic anemia patients - Chen-Yuan Li; Dan-Dan Chen; Xin-Yan Zhang; Shu-Qian Tang; Meng-Zhu Shen; Ya-Ting Yu; Zhi-Wei Zhang; Zheng-Li Xu; Yuan-Yuan Zhang; Jin-Song Jia; Lan-Ping Xu; Yu Wang; et al. (Science China Life Sciences, 2026)

Regulatory patterns and driving factors of soil aggregates on the environmental behavior of heavy metals: A global study based on meta-analysis and machine learning - Yu-Xuan Song; Yuhan Meng; Bingxuan Zhao; Tian-Hao Che; Zining Li; Zuozhou Yu; Xinyang Zhen; Yining Li; Chengyong Li; Quan-Ying Wang; Jing-Ya Zhou (Environmental Geochemistry and Health, 2026)

Research on the Adaptive Response Mechanism of Bacterial Infection in Triplophysa siluroides - Yuanliang Duan; Ya Liu; Jun Ou; Feiyang Li; Xiaoyun Wu; Jianshen Lai; Jian Zhou; Mingjiang Song (Fishes, 2026)
Triplophysa siluroides, a unique species of plateau fish, holds significant economic value. However, its natural population has sharply declined due to overfishing and the construction of water conservancy projects. Investigating the various conditions necessary for its growth is a crucial prerequisite for successful artificial breeding. This study used Edwardsiella tarda as the pathogenic bacterium to determine the median lethal concentration following infection of T. siluroides, as well as to examine changes in tissues, organs, and gene expression. The study found that dead T. siluroides displayed symptoms such as abdominal distension, fluid accumulation, and a reddened anus, and the median lethal concentration of E. tarda for T. siluroides was calculated to be 1.00 × 106 CFU/mL. Following infection with E. tarda, the liver, intestine, gills, spleen, and kidneys exhibited varying degrees of lesions. Transcriptome sequencing identified a total of 54,667 genes. Compared to the blank control group, 192 genes were downregulated and 125 genes were upregulated in T. siluroides infected with E. tarda. In contrast, after infection with the poly(I:C) viral mimic, 225 genes were downregulated and 436 genes were upregulated. This study determined the median lethal concentration of E. tarda for T. siluroides via intraperitoneal injection under laboratory conditions. The results may contribute to disease prevention and control in the breeding of T. siluroides, as well as inform future risk assessments of infection in aquaculture water bodies.

Corrigendum to “Acanthoic acid protectsagainst ethanol-induced liver injury: Possible role of AMPK activation and IRAK4 inhibition” [Toxicol. Lett. 281 (2017) 127–138] - You-Li Yao; Xin Han; Jian Song; Jing Zhang; Ya-Mei Li; Li-Hua Lian; Yan-Ling Wu; Ji-Xing Nan (Toxicology Letters, 2026)

High-voltage-tolerant zirconium-organic nanosheet separator enabling 5 V LiNi0.5Mn1.5O4|Li batteries with enhanced capacity density - Jian-Qiang Shen; Ya-Nan Gao; Ying-Li Song; Lingjuan Zhang; Gen Chen; Guoqiang Tan; Yunfeng Lu; Xian-Ming Zhang (Chemical Engineering Journal, 2026)

A novel dual-function biosensor based on polarity reversal of MFC for bioelectricity generation and detecting trimethylamine-N-oxide - Sheng-chao Gao; Yu-xuan Wang; Yong-dong Li; Ru-meng Zhang; Ya-nan Zhang; Jin-song Dong; Hong-xia Ni; Yi Chen; Xi-hui Shen; Ying Liu (Chemical Engineering Journal, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

Shrub Encroachment Constrains Precipitation‐Driven Shifts in Herbaceous Biomass‐Diversity Relationships - Hailing Li; Xiaoan Zuo; Fons van der Plas; Ya Hu; Fangwei Hao; Hongling Yang; Xiangyun Li; Ping Yue; Shaokun Wang; Zhaobin Song; Rentao Liu; Jiansheng Ye; et al. (Global Change Biology, 2026)
The relationship between herbaceous above ground biomass and species richness typically exhibits a unimodal pattern, shifting from positive under low‐precipitation conditions to negative under high‐precipitation conditions. While shrub encroachment generally reduces both herbaceous aboveground biomass and diversity, how shrubs mediate the herbaceous biomass‐richness relationship under altered precipitation regimes remains unclear. By synthesizing data from globally distributed precipitation manipulation experiments, we reveal contrasting herbaceous biomass‐diversity responses in grasslands and shrublands. In grasslands, reduced precipitation shifts the peak of the unimodal herbaceous biomass‐richness curve toward lower biomass, whereas increased precipitation shifts it toward greater biomass. In contrast, the peak of the unimodal relationship in shrub‐dominated systems shows no significant shifts across precipitation extremes. These global patterns are supported by a 5‐year field experiment in a desert steppe in Northern China, which further shows that precipitation change strongly affects species richness through soil water availability in grasslands, while exerting weaker effects through modifications of the fast‐slow leaf economics spectrum in shrublands. These findings demonstrate that shrub encroachment can constrain precipitation‐induced changes in herbaceous biomass‐diversity relationships, providing important insights into how woody plant expansion interacts with climate change to influence ecosystem structure and function.

Potential role of AHL-mediated quorum sensing in filamentous bulking induced by Sphaerotilus natans in the activated sludge process with low dissolved oxygen - Yi Fu; Wei-Xin Liu; Shao-Yang Liu; You-Peng Chen; Song-Ya Li; Fang Fang; Jin-Song Guo; Peng Yan (Journal of Environmental Chemical Engineering, 2026)

Revealing the metabolic mechanism of enzymatic hydrolysis products of boletus edulis bull.: Fr. Based on random forest integration multi-omics - Ningjing Guo; Xiang Li; Ya Dai; Xue Li; Qian Yao; Hua Lin; Mingjing Song (Food Chemistry, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Cell type-specific contribution of low-density lipoprotein receptor to atherosclerosis - Wei-Hui Li; Yu-Liang Zhang; Ya-Fen Zhang; Zhenyang Yu; Liang Chen; Hao-Yu Fang; Liang Cheng; Bao-Liang Song; Jie Luo (Science China Life Sciences, 2026)

Intelligent stratigraphic identification based on real-time construction parameters from rotary drilling rigs - Chao-Ji Li; He Yang; Fei Ren; Hong-Ya Yue; Xiu-Guang Song; Li-Min Li; Pei-Zhi Zhuang (Bulletin of Engineering Geology and the Environment, 2026)

Highly efficient biological reduction of Se(IV) in S0-based reactors under two nutrient conditions: multilevel synergistic mechanism and engineering applications - Song Yu; Wei Jiang; Ting-ting Guo; Hai-bo Li; Yuan-yuan Song; Zhi Chen; Ya-nan Hou; Bo Ren; Jian-bo Guo (Chemical Engineering Journal, 2026)

Behaviorally inspired by blue-whale throat-pleats during filter feeding: A thermoresponsive hydrogel for achieving efficient solar-driven cyclic water release and purification - Yan-Shu Xiong; Mei Li; Tanli Lu; You-Ya Sun; Hai-Qin Lu; Wen Li; He Liu; Zhanqian Song (Chemical Engineering Journal, 2026)

Spring frost frequency increased in North America but decreased in Eurasia from 1948 to 2016 - Wei Guo; Chuhan Lu; Ping Xia; Lijiang Fu; Govindjee Govindjee; Hao Tang; Jian Chen; Li Song; Jinglu Tan; Zhenyu Xu; Ya Guo (Theoretical and Applied Climatology, 2026)

Integrated transcriptomic and metabolomic analyses reveal the molecular adaptive mechanisms of Schizopygopsis chengi baoxingensis under acute heat stress - Hangyu Lin; Xiaoyun Wu; Ya Liu; Jun Ou; Luyun Ni; Feiyang Li; Jiansheng Lai; Quan Gong; Jue Lin; MingJiang Song (Journal of Thermal Biology, 2026)

Biomimetic rehabilitation of damaged contaminant-containment and load-bearing structure by a near-zero disturbance method: Pilot-scale test in an operating plant - Ya-song Feng; Shui Wang; Yu-tao Chen; Meng-ya Li; Zhi-hua Yin; Zong-xiang Lv (Journal of Cleaner Production, 2026)

Small-strain stiffness of in situ granite residual soil: Experimental comparison under biased and isotropic consolidation - Song Yin; Ya He; Sen Li; Siyue Zheng; Xianwei Zhang; Xinming Li (Soil Dynamics and Earthquake Engineering, 2026)

Bright and stable green-emitting quantum dots with universal surface modifiability for diagnostic probes - Ning Li; Dexia Zhou; Ya Liu; Ziming Zhou; Zhaobing Tang; Siqi Jia; Ruili Wu; Huaibin Shen; Yanbing Lv; Lin Song Li (Chemical Engineering Journal, 2026)

Prediction Of Relative Permeability Curve Based On Machine Learning Driven By Logging Data - Jia-ru Zou; Shou-dong Huo; En-liang Liu; Tong-sheng Zeng; Lian-lian Hu; Ya-ying Song; Meng Li (Applied Geophysics, 2025)

Combined toxicity of microplastics and heavy metals to terrestrial plants: A global meta-analysis integrating machine learning predictions - Ye-Qian Zhen; Tian-Hao Che; Yu-Xuan Song; Ya-Ming Wan; Hai-Han Jiang; Zuo-Zhou Yu; Miao Yu; Shi-Qi Xu; Cheng-Yong Li; Jing-Ya Zhou (Journal of Environmental Chemical Engineering, 2025)

Phenytoin quaternary ammonium salt is a novel wound treatment drug with both pro-healing and antibacterial effects - Yuchen Li; Jiaming Cui; Peihui Zhou; Bixuan Cao; Li Zhao; Weize Kong; Xueheng Sun; Ya Fang; Jinwu Wang; Mingzhi Song; Li Wang (Chemical Engineering Journal, 2025)

A facile and universal ligand exchange strategy enables sequential surface functionalization of quantum dots for high quality in vivo imaging - Xue-Hui Shi; Zhendong Zhu; Changlin Shen; Ya Li; Zhuang Qian; Yonghao Wu; Huifeng Chen; Qing-Qing Ye; Chaojie Hu; Yifan Song; Lei Wang; Zhimou Yang; et al. (Chemical Engineering Journal, 2025)

Volatile organic compounds in various workplaces and during commutes in a Chinese city: occurrence and health risks for different occupations - Jin-Long Mai; Yi Yang; Yuan Zeng; Song Liu; Zhen-Shan Huang; Jia-Hua Wu; Ya-Jing Li; She-Jun Chen (Environmental Research, 2025)

Functional miRNA-mRNA Regulatory Modules in the Head Kidney of Pelteobagrus vachellii in Response to Aeromonas veronii Infection - Feiyang Li; Xiaoyun Wu; Yeyu Chen; Qiaolin Zou; Pengcheng Li; Mingjiang Song; Quan Gong; Ya Liu; Jiansheng Lai; Luyun Ni; Jun Wang (Fishes, 2025)
Aeromonas veronii is a major pathogen threatening freshwater aquaculture, yet the molecular mechanisms of Pelteobagrus vachellii’s immune response to this infection remain unclear. This study integrated histopathology, mRNA-seq and small RNA-seq to investigate P. vachellii’s response to A. veronii at 48 h post-challenge. Histopathologically, infection induced gill epithelial detachment, hepatocyte swelling with cytoplasmic vacuolation, and melanomacrophage centers (MMCs) in the mid-kidney (histological assessment of the head kidney was not feasible due to sampling limitations associated with its small size). Transcriptomic analysis identified 1210 differentially expressed genes (DEGs) in the head kidney (819 downregulated, 391 upregulated), significantly enriched in 11 immune pathways (e.g., NF-κB, Th17 cell differentiation, Complement and coagulation cascades), with key immune genes (e.g., IL-1β, TCRα, CCL4) upregulated. Gene Set Enrichment Analysis (GSEA) revealed activation of the proteasome, ribosome and oxidative phosphorylation pathways, and suppression of the autophagy-animal, FoxO and AMPK pathways. Small RNA-seq identified 544 known and 958 novel miRNAs in the head kidney, with 42 downregulated and 36 upregulated differentially expressed miRNAs (DE miRNAs). The miRNA-mRNA network showed that DE miRNAs (e.g., miR-101-y/z, miR-132-z, miR-3167-y) negatively regulated immune-related target genes (IL-1R1, IRF4, IκBα) in core immune pathways. Collectively, this study clarifies the pathological and miRNA-mRNA regulatory modules of P. vachellii head kidney against A. veronii infection, providing valuable information that enables the further analyses of the defense mechanisms of P. vachellii against A. veronii infection.

High efficacy of (Z)-ligustilide in inhibiting postharvest apple ring rot and its antifungal mechanism against Botryosphaeria dothidea - Xiao-Yi Tong; Li-Li Song; Hui-Fang Du; Ya-Hui Zhang; Jia-Wen Shou; Cai-Juan Zheng; Wen-Bin Gao; Zhong-Cheng Liu; Du-Qiang Luo; Yun-Feng Liu; Fei Cao (Postharvest Biology and Technology, 2025)

Preparation and flavor quality analysis of high-antioxidant activity enzymatic hydrolysate of Boletus edulis - Ningjing Guo; Ya Dai; Xue Li; Mingjing Song; Xiang Li; Ting Bai (Food Bioscience, 2025)

High-entropy sulfide and nanozyme hybrid system with synergistic interface-engineering: Ultra-sensitive photoelectrochemical detection of chloramphenicol - Yi-Hong Chen; Ai-Jun Wang; Ya-Cheng Shi; Li-Ping Mei; Pei Song; Tiejun Zhao; Jiu- Ju Feng (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Proteome Profiling of Serum Reveals Pathological Mechanisms and Biomarker Candidates for Cerebral Small Vessel Disease - Yun-chao Wang; Hang-hang Zhu; Liu-Chang He; Ya-ting Yao; Lei Zhang; Xin-li Xue; Jing-yi Li; Li Zhang; Bo Song; Chang-he Shi; Yu-sheng Li; Yuan Gao; et al. (Translational Stroke Research, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Acetamiprid mediates cognitive dysfunction through the gut-brain axis: Synaptic damage and immune-mediated blood-brain barrier dysfunction - Bing Wu; Xue-yan Tian; Wen-si Ni; Hao-Xuan Gao; Yu-wen Wang; Ling-he Zhang; Yu-bin Li; Yan-ling Lv; Ya-nan Song; Yu-cheng Yan; Xiao-zhe Geng; Yi-man Li; et al. (Journal of Hazardous Materials, 2025)

Transmembrane uptake of polystyrene nanoplastics mediated by aquaporin in tartary buckwheat: Physiological consequence and genomic mechanism - Yu-Kang Hou; Shuo Gao; Qiang Lai; Wen-Rui Lu; You-Bao Cai; Ya-Wen Yuan; Si-Yuan Yao; Hong-Yan Tao; Li-Zhe An; You-Cai Xiong; Yuan Song (Journal of Hazardous Materials, 2025)

Thiazole-fused thiazoliniums with ketone warheads as covalent inhibitors targeting Cys44 of SARS-CoV-2 3CLpro - Qizhen Cao; Zhaoqin Zhang; Guanghao Zhu; Sanfeng Dong; Xue Sun; Yuqing Song; Ya Zhang; Tingting Cai; Xinben Zhang; Yong Zhang; Zhijian Xu; Ruisheng Xiong; et al. (Chemico-Biological Interactions, 2025)

Production of docosahexaenoic acid from corncob residue wastes through integrated whole-cell lignocellulosic saccharification and lipid fermentation by Aurantiochytrium - Xiaojin Song; Weijian Wan; Yuedong Zhang; Guang Yu; Bin Li; Qiu Cui; Ya-Jun Liu; Yingang Feng (Bioresource Technology, 2025)

Molecular characterization of a novel chrysovirus isolated from the phytopathogenic fungus Fusarium commune - Wen Xin Huang; Li E Yang; Yan Bin Huang; Tao Sha Xu; Jie Zhong; Ya Rong Wang; Yan Song Xiao (Archives of Virology, 2025)

Surface-enhanced fluorescence-encoded nanoprobes for contrast-enhanced single-cell imaging of gene expression - Lulu Song; Shuang Li; Chaojie Su; Ya Wang; Yifu Wang; Yiqiong Hu; Yamin Xiong; Leiliang He (Chemical Engineering Journal, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

Study on the mechanism of slow-release antioxidant inhibitor in inhibiting coal spontaneous combustion - Teng Ma; Binbin Ma; Xiaowei Zhai; Bobo Song; Ya-E Bai; Le Hao; Xintian Li; Qinyuan Hou; Xiaokun Chen (Fuel, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Seismotectonic characteristics of the 1976 M 7.8 Tangshan earthquake sequence revealed by high-resolution tomography - Chenghao Jiang; Zhiwei Li; Feng Bao; Jian Zhang; Tianyao Hao; Yufeng Deng; Ya Xu; Song Huang (Tectonophysics, 2025)

Recovery of metal elements from spent lithium batteries using their inherent “Lattice redox energy” - Honghuai Sun; Huiliang Hou; Qingming Song; Ya Liu; Bang Li; Zhenming Xu (Resources, Conservation and Recycling, 2025)

Time series comparative genomics analysis reveals the adaptive evolution of caproic acid-producing bacteria to the long-term liquor brewing environment - Gan-Lin Li; Jun-Lan Mei; Li-Juan Chai; Xiao-Zhong Zhong; Ya-Ning Song; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2025)

Greenness, nighttime light, and couple fecundability: A national cohort study between 2014 and 2020 - Mengyao Li; Xinghou He; Bin Zhang; Hongbing Xu; Jianbin Wu; Xuyang Shan; Ya Zhang; Huiying Xu; Hongguang Zhang; Yuan He; Yan Fang; Zuoqi Peng; et al. (Environmental Research, 2025)

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

PRDX1 affects acrylamide-induced neural damage through the PTEN/AKT signaling pathway - Dong-Xue Fu; Ya-Ting Lei; Hai-Bo Guo; Ting Chen; Xiang-Ying Gao; Xiao-Li Wang; Xiang Huang; Ling-Ling Song; Sheng-Yuan Wang; Qin-Xue Dai (NeuroToxicology, 2025)

Polygonatum cyrtonema Hua polysaccharide alleviates ulcerative colitis via gut microbiota-independent modulation of inflammatory immune response - Jin-Yang Shi; Yong-Jian Wang; Qian-Wen Bao; Ya-Min Qin; Pei-Pei Li; Qiao-Qiao Wu; Cheng-Kai Xia; De-Ling Wu; Song-Zi Xie (Carbohydrate Polymers, 2025)

A chemiluminescence immunoassay for detection of Toxoplasma gondii antibody in porcine based on GRA6 and SAG1 - Ran Wu; Ya-Fei Song; Yanlong Gu; Jiang Li; Zhipeng Niu; Dong-Hui Zhou (Veterinary Parasitology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Enhancing nitrogen removal performance of anammox granular sludge with ascorbic acid at low temperatures - Meng-Jia Zhu; Song-Ya Li; Li-Li Qiao; You-Peng Chen; Jin-Song Guo; Shao-Yang Liu; Peng Yan (Journal of Environmental Management, 2025)

Filamentous bacteria in activated sludge: Geographic distribution and impact of treatment processes - Rui Liu; Yang Chen; Song-Ya Li; You-Peng Chen; Jin-Song Guo; Shao-Yang Liu; Peng Yan (Journal of Environmental Management, 2025)

Application of microfluidics for revealing physiological metabolic response of algae at the single-cell level - Yu-Fen Qiao; Song-Ya Li; Ting-Ting Liu; You-Peng Chen; Jin-Song Guo; Shao-Yang Liu; Peng Yan (Journal of Environmental Chemical Engineering, 2025)

Vanadium-Based Prussian blue analogue for high energy aqueous Zinc-Iodine batteries - Wenjie Li; Peng Hei; Ya Sai; Jianming Meng; Yang Yu; Yu Song; Xiao-Xia Liu (Chemical Engineering Journal, 2025)

Correction to: Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2025)

Resource-enhancing global changes shift soil multifunctionality towards faster cycling in arid grasslands - Zhaobin Song; Xiaoan Zuo; Shaokun Wang; Xiangyun Li; Ya Hu; Jingjuan Qiao; Chao Wang; Ellen L. Fry; Jordi Sardans; Josep Peñuelas; Yann Hautier (Applied Soil Ecology, 2025)

Groundwater health risks and water quality assessment in the sources of many mighty rivers in Asia: Ngari, Tibet - Fei He; Shehong Li; Lian Song; Qiao Han; Dan Zeng Ya Jie; Yong Shui; Jen-How Huang (Process Safety and Environmental Protection, 2025)

Hazardous electrolyte releasement and transformation mechanism during water protected spent lithium-ion batteries crushing - Bang Li; Tingjin Zhou; Honghuai Sun; Qingming Song; Ya Liu; Jia Li; Zhenming Xu (Journal of Hazardous Materials, 2025)

Potential roles of quorum quenching in microbial aggregates during wastewater treatment - Yi Fu; Song-Ya Li; Yang Chen; You-Peng Chen; Jin-Song Guo; Shao-Yang Liu; Peng Yan (Bioresource Technology, 2025)

Unveiling the metabolic heterogeneity and formation mechanism in Chinese typical Daqu based on Qu-omics - Yu Mu; Shangjie Yao; Ying Huang; Zhiyu Zhu; Dong Li; Ya Song; Zehuan Liu; Chunlin Zhang; Shirui Yu (Food Research International, 2025)

Corrigendum to “Platelet-rich plasma/chitosan/chondroitin sulfate immunomodulatory hydrogel co-networks for diabetic wound repair: Functions and molecular mechanisms” [Chem. Eng. J. 491 (2024) 152138] - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2025)

Enhancing the adaptation of anammox bacteria at low temperature: Alleviating the oxidative damage to anammoxosome membrane by ascorbic acid - Yu-Tong Xiong; Song-Ya Li; Shao-Yang Liu; Li-Li Qiao; You-Peng Chen; Peng Yan (Chemical Engineering Journal, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

The effect of nitrogen input on methane uptake in a wet and a dry year from a temperate desert steppe - Ping Yue; Kaihui Li; Ya Hu; Jingjuan Qiao; Zhaobin Song; Shaokun Wang; Tom Misselbrook; Xiaoan Zuo (Agricultural and Forest Meteorology, 2025)

N-methyl-D-aspartate Receptor Subunits 2A and 2B Mediate Connexins and Pannexins in the Trigeminal Ganglion Involved in Orofacial Inflammatory Allodynia during Temporomandibular Joint Inflammation - Yue-Ling Li; Yan-Yan Zhang; Qin-Xuan Song; Fei Liu; Ya-Jing Liu; Yi-Ke Li; Cheng Zhou; Jie-Fei Shen (Molecular Neurobiology, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Dual emission chiral carbon dots as fluorescent probe for fast chiral recognition of tryptophan enantiomers - Qi Wu; Yuan Chen; Yan-Li Wang; Ji-Ying Song; Hai-Tao Lv; Ya-Ming Sun (Analytica Chimica Acta, 2025)

Precipitation-induced biomass enhancement and differential allocation in Inner Mongolia's herbaceous and shrub communities - Xiangyun Li; Ya Hu; Zhaobin Song; Ping Cong; Huan Cheng; Xuebo Zheng; Wenjing Song; Ping Yue; Shaokun Wang; Xiaoan Zuo (Science of The Total Environment, 2024)

Electric fields and transglutaminase in preparing adzuki bean protein emulsion gel for plant-based steamed egg custard - Qian Li; Tingyu Song; Yongxin Yu; Yiping Ren; Jian-Ya Qian (Innovative Food Science & Emerging Technologies, 2024)

Lignanamides: A comprehensive review of chemical constituents, biological activities, extraction methods and synthetic pathway - Jing Sun; Li-Tao Tong; Peng-Fei Tu; Lin-Lin Chen; Xin Xu; Ya Song; Xin-Xin Yang; Zi-Bin Guo; Xiang Zou; Chen-Xin Sun; Yan Mi; Bei Fan; et al. (Food Chemistry, 2024)

Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2024)

Plant Functional Traits Modulate Effects of Drought on C:N:P Stoichiometry of Plant, Litter, and Soil Microbe in an Arid Grassland - Zhaobin Song; Xiaoan Zuo; Xueyong Zhao; Xiangyun Li; Ya Hu; Jingjuan Qiao; Ping Yue; Min Chen; Shaokun Wang; Jordi Sardans; Josep Peñuelas (Journal of Soil Science and Plant Nutrition, 2024)

New insights into microalgal photobiological hydrogen production: Potential role of aggregation forms in modulating the hydrogenase activity and metabolic properties of microalgae during hydrogen production - Xu Wang; Song-Ya Li; Yang chen; You-Peng Chen; Jin-Song Guo; Shao-Yang Liu; Peng Yan (Chemical Engineering Journal, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

A One-Nano MOF-Two-Functions Strategy Toward Self-healing, Anti-inflammatory, and Antibacterial Hydrogels for Infected Wound Repair - Ya-Ling Fan; Hong-Jie Liu; Zi-Li Wang; Zi-Lin Wang; Li-Li Zhu; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Dominant role of soil iron and organic matters in arsenic transfer from soil to plant in a mine area in Hunan Province, Central China - Yang Song; Fenglin Zhang; Haipu Li; Ya Gao; Yang Liu; Zhaoxue Zhang; Ying Fang; Xinghao Liu; Zhaoguang Yang (Environmental Science and Pollution Research, 2024)

Selenium nanoparticles alleviates cadmium induced hepatotoxicity by inhibiting ferroptosis and oxidative stress in vivo and in vitro - Chunyan Shao; Tongwang Luo; Shujie Wang; Zhuoyue Li; Xiaoqiang Yu; Ya Wu; Sheng Jiang; Bin Zhou; Quanjiang Song; Shengzhe Song; Xiaodu Wang; Houhui Song (Chemosphere, 2024)

Salinity responsive mechanisms of sulfur-based mixotrophic denitrification and ectoine induced tolerance enhancement - Ran Li; Ya-Nan Hou; Haibo Li; Yi Han; Daohong Zhang; Yuanyuan Song; Cong Huang; Jianbo Guo; Zhihua Liu; Wei Wei; Bing-Jie Ni (Chemical Engineering Journal, 2024)

Heterometallic Eu/Zn-MOF-based ratiometric sensing platform: Highly sensitive fluorescence / second-order scattering identification of tetracycline analogs and its molecular informatization applications - Ya Jie Fan; Jiang Xue Dong; Tan Liu; Yan Qing Chang; Yong Sen Zhao; Yan Lei Li; Sai Mei Zhang; Song Yun Cao; Ming Su; Shi Gang Shen; Zhong Feng Gao (Analytica Chimica Acta, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Hydroxyl-containing triazine-based conjugated microporous polymers for solid phase extraction of fluoroquinolone antibiotics in the environment and food samples - Lu-Shu Meng; Xiao-Li Wang; Xia Wang; Lei Ji; Lei-Lei Wang; Ya-Qi Cai; Ru-Song Zhao (Food Chemistry, 2024)

Platelet-Rich Plasma/Chitosan/Chondroitin sulfate immunomodulatory hydrogel Co-Networks for diabetic wound Repair: Functions and molecular mechanisms - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Drp1: Focus on Diseases Triggered by the Mitochondrial Pathway - Fulin Sun; Min Fang; Huhu Zhang; Qinghang Song; Shuang Li; Ya Li; Shuyao Jiang; Lina Yang (Cell Biochemistry and Biophysics, 2024)

Osiris17 is indispensable for morphogenesis of intestinal tract in Locusta migratoria - Wei Dong; Chen-Yang Song; Ya-Nan Li; Xu-Bo Zhang; Jian-Zhen Zhang (Pesticide Biochemistry and Physiology, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Environmental exposure to per- and polyfluoroalkyl substances mixture and asthma in adolescents - Yi-Fan Wang; Li Li; Xu Wang; Ya-Nan Yun; Xue-Lin Wang; En-Yang He; Ming-Kun Song; Xue-Hong Xia; Ying-Xue Zou (International Archives of Occupational and Environmental Health, 2024)

Stronger deterministic processes shape the plastisphere microbiota of biodegradable microplastics compared to non-biodegradable microplastics in farmland soil - Yu Zhang; Jun Ma; Ya-Qiong Song; Gang Li; Patrick O'Connor (Applied Soil Ecology, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Plant functional traits mediate the response magnitude of plant-litter-soil microbial C: N: P stoichiometry to nitrogen addition in a desert steppe - Zhaobin Song; Xiaoan Zuo; Xueyong Zhao; Jingjuan Qiao; Hu Ya; Xiangyun Li; Ping Yue; Min Chen; Shaokun Wang; Eduardo Medina-Roldán (Science of The Total Environment, 2024)

Removal of Bismuth from Water by Orange Peel Biochar - Adil Abbas Kareem; Yu-liang Liao; Ya-qi Yu; Ning Ning; Shan-shan Guo; Qiao-yu Song; Jia-li Li; Jin-yan Yang (Water, Air, & Soil Pollution, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Clerodane diterpenoids with in-vitro anti-neuroinflammatory activity from the tuberous root of Tinospora sagittata (Menispermaceae) - Jia-Qi Song; Kai-Cheng Yang; Xian-Zhe Fan; Li Deng; Yang-Li Zhu; Hong Zhou; Ya-Si Huang; Xiang-Qian Kong; Li-Jun Zhang; Hai-Bing Liao (Phytochemistry, 2024)

Highly efficient ionic thermally activated delayed fluorescence emitters with short exciton lifetimes towards High-Performance Solution-Processed OLEDs - Ya-Shu Wang; Xin Lu; Jin-Hui Song; Xiao Li; Xiao-Dong Tao; Lingyi Meng; Xu-Lin Chen; Can-Zhong Lu (Chemical Engineering Journal, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

Retraction Note: Autophagy regulated by lncRNA HOTAIR contributes to the cisplatin-induced resistance in endometrial cancer cells - Meng-Yao Sun; Jian-Yong Zhu; Chun-Yan Zhang; Miao Zhang; Ya-Nan Song; Khalid Rahman; Li-Jun Zhang; Hong Zhang (Biotechnology Letters, 2024)

Expansion of YALIcloneHR toolkit for Yarrowia lipolytica combined with Golden Gate and CRISPR technology - Qi Shen; Fang Yan; Ya-Wen Li; Jian Wang; Jia Ji; Wen-Xin Yan; Dan-Chen He; Ping Song; Tian-Qiong Shi (Biotechnology Letters, 2024)

Comparison of muscle structure and transcriptome analysis reveals the mechanism of growth variation in Yangtze sturgeon (Acipenser dabryanus) - Qingzhi Li; Jun Wang; Yeyu Chen; Xiaoyun Wu; Ya Liu; Jiansheng Lai; Mingjiang Song; Feiyang Li; Pengcheng Li; Bin He; Bin Wang; Tao Yan; et al. (Aquaculture, 2024)

Drought intensity and post-drought precipitation determine vegetation recovery in a desert steppe in Inner Mongolia, China - Xiangyun Li; Zhaobin Song; Ya Hu; Jingjuan Qiao; Yuheng Chen; Shaokun Wang; Ping Yue; Min Chen; Yuguang Ke; Chong Xu; Qiang Yu; Xiaoan Zuo (Science of The Total Environment, 2024)

Caffeic acid-grafted chitosan/sodium alginate/nanoclay-based multifunctional 3D-printed hybrid scaffolds for local drug release therapy after breast cancer surgery - Ya Su; Yaqian Liu; Xueyan Hu; Yueqi Lu; Jinyuan Zhang; Wenbo Jin; Wang Liu; Yan Shu; Yuen Yee Cheng; Wenfang Li; Yi Nie; Bo Pan; et al. (Carbohydrate Polymers, 2024)

The response of rhubarb to smut infection is revealed through a comparative transcriptome and metabolome study - Shuangshuang Zhou; Ya Lin; Yu Cai; Linfang Li; Xiaohui Yao; Kuan Sun; Qin Song; Qingwei Zhang (Planta, 2024)

Isolation and characterization of 55 SNP markers in Triplophysa (Hedinichthys) yarkandensis macroptera - Qiang Li; Yeyu Chen; Hongyu Ke; Zhongmeng Zhao; Han Zhao; Jiansheng Lai; Xiaoyun Wu; Mingjiang Song; Feiyang Li; Ya Liu (Conservation Genetics Resources, 2023)

Investigation of the acicular aragonite growth behavior in AOD stainless steel slag during slurry-phase carbonation - Ya-Jun Wang; Jun-Guo Li; Meng-Jie Tao; Xi Zhang; Jian-Bao Zhang; Song Qin; Shao-Hua Liu; Li-Jie Peng; Xiao-Pei Zhang; Ya-Nan Zeng (Science of The Total Environment, 2023)

The sound and surprise: overlapping meta-analyses on the topic of safety and efficacy of PD-1 and PD-L1 inhibitors in the treatment of non-small cell lung cancer - Shun-Long Ou; Jing Luo; Song Wang; Kai-Yue Li; Su-Ya Du; Qian Jiang (European Journal of Clinical Pharmacology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Prevalence of paratuberculosis in cattle in China: A systematic review and meta-analysis - Na Lu; Ya-Ling Niu; Yang Song; Dan-Dan Zhang; Jing Jiang; Jiaqi Wei; Hong-Li Geng; Hongwei Cao (Preventive Veterinary Medicine, 2023)

Integrated metabolomic and transcriptomic responses to heat stress in a high-altitude fish, Triplophysa siluroides - Yeyu Chen; Xiaoyun Wu; Pengcheng Li; Ya Liu; Mingjiang Song; Feiyang Li; Jun Ou; Jiansheng Lai (Fish & Shellfish Immunology, 2023)

Isolation and characterization of 73 SNP markers in Schizopygopsis chengi baoxingensis - Mingjiang Song; Yeyu Chen; Xiaoyun Wu; Ya Liu; Feiyang Li; Quan Gong; Jun Ou; Pengcheng Li; Qiaolin Zou; Jiansheng Lai (Conservation Genetics Resources, 2023)

Valbenazine promotes body growth via growth hormone signaling during zebrafish embryonic development - Zhengkang Su; Ziru Dai; Fengqing Qin; Hai Zhang; Miaomiao Zheng; Ya Zhu; Zhiqian Tong; Weihong Song; Xi Li (Toxicology and Applied Pharmacology, 2023)

Temperature-dependent NO2/diisopropylamine sensor based on SnO2 squama-wrapped tubes derived from waste bamboo shoot skin - Bao-Yu Song; Cong Chen; Ya-Nan Li; Xian-Fa Zhang; Xiao-Li Cheng; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Proteomic and Functional Analyses of Outer Membrane Vesicles Secreted by Vibrio splendidus - Huimin Song; Yilong Ruan; Ya Li; Huirong Yang; Weiwei Zhang (Journal of Ocean University of China, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

An extracellular matrix-inspired self-healing composite hydrogel for enhanced platelet-rich plasma-mediated chronic diabetic wound treatment - Ya Zhang; Zi-Li Wang; Ze-Peng Deng; Zi-Lin Wang; Fei Song; Li-Li Zhu (Carbohydrate Polymers, 2023)

Publisher Correction: Functions of RNA N6-methyladenosine modification in cancer progression - Bing Chen; Ya Li; Ruifeng Song; Chen Xue; Feng Xu (Molecular Biology Reports, 2023)

Thirty years of research on photoacoustic imaging in the field of cancer: A scientometric analysis of hotspots, bursts, and research trends - Zhifan Li; Ya Gao; Jinhui Tian; Qihua Song; Mingyuan Wang; Junqiang Lei (Environmental Science and Pollution Research, 2023)

Enhanced vitamin K2 production by engineered Bacillus subtilis during leakage fermentation - Meng-jie Zhou; Jing Wu; Liu-xiu Hu; Wen-song Hu; Jun-bao Huang; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Zheng-lian Xue; Yan Liu (World Journal of Microbiology and Biotechnology, 2023)

Study on the influence of key active groups on gas products in spontaneous combustion of coal - Teng Ma; Xiao-Wei Zhai; Yang Xiao; Ya-E Bai; Kun Shen; Bo-Bo Song; Le Hao; Li-Feng Ren; Xiao-Kun Chen (Fuel, 2023)

Establishment of a lipopolysaccharide-induced inflammation model of human fetal colon cells - Keqi Yu; Shengtao Liao; Chuanfei Li; Ya Song; Zhechuan Mei; Lin Lv (Molecular Biology Reports, 2023)

Sequence Stratigraphy, Sedimentology, and Reservoir Characteristics of the Middle Cretaceous Mishrif Formation, South Iraq - Leifu Zhang; Wenqi Zhang; Yong Li; Benbiao Song; Dawang Liu; Ya Deng; Jiacheng Xu; Yuning Wang (Journal of Marine Science and Engineering, 2023)
The Cenomanian–Early Turonian Mishrif Formation is a great contributor to oil production in Iraq. Integrating petrographic, mineralogical, and wireline logging data from 52 wells, this study provides an improved understanding of the sequence stratigraphy, depositional evolution, and reservoir characteristics of the Mishrif Formation in the Mesopotamian Basin, south Iraq. Five types of facies associations are classified: lagoon, shoal, rudist bioherm, shallow marine, and deep marine. Such a classification allows convenient differentiation and interpretation of wireline logs. A sequence stratigraphic framework including five third-order sequences (Mhf 1 to Mhf 5) for the Mishrif Formation is established mainly using wireline logging data of close-distance wells, with the aid of cores and thin sections. Two end-member depositional evolution stages are recognized, from clinoform-like progradational shoal complexes in Mhf 1 within a shallow marine environment, to tidal channels in Mhf 2–3 within a lagoon environment. For Mhf 4–5, abrupt changes in facies associations from north to south indicate the development of an intra-shelf basin where organic-rich mudstones directly overlie the shallow marine grainstone shoals and lagoonal wackestones. Reservoir characteristics and compartmentalization are directly controlled by the sequence stratigraphic framework. Sequence boundaries are featured by wackestones and mudstones overprinted by cementation; they are regionally correlatable and work as regional barriers. Shoal complexes in Mhf 1 and tidal channels in Mhf 2–3 are the main reservoir units. Mudstones and wackestones are intra-reservoir baffles and become more frequently developed towards the south, reflecting the increasing water depth towards south. The characterization of the tidal channels, clinoform-like shoals, and intrashelf basinal deposits in the current study could benefit later development of the Mishrif Formation.

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Isolation and characterization of 46 SNP markers in Gymnocypris chilianensis - Ya Liu; Wenqiong Wu; Siyi Zhu; Yeyu Chen; Xiaoyun Wu; Jiansheng Lai; Mingjiang Song; Feiyang Li; Qiang Li (Conservation Genetics Resources, 2023)

Heavy metals in riverine/estuarine sediments from an aquaculture wetland in metropolitan areas, China: Characterization, bioavailability and probabilistic ecological risk - Hai-Song Li; Yang-Guang Gu; Rui-Ze Liang; Ya-Su Wang; Richard W. Jordan; Liang-Gen Wang; Shi-Jun Jiang (Environmental Pollution, 2023)

Engineering spatial locations of Pt in hierarchically porous KL zeolite by atomic layer deposition with enhanced n-heptane aromatization - Shuyuan Wang; Ya Gao; Li Wei; Mengxia Yan; Fengjiao Yi; Jianmei Wang; Luyuan Wang; Guofu liu; Angang Song; Yan Li; Feipeng Cai; Di Zhu; et al. (Fuel, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

High-efficient fire-safe epoxy enabled by bio-based atomic-level catalytic engineering - Lin-Yun Jiang; Zhi Li; Ya-Min Liang; Qing-Qing Bi; Song Tian; Shao-Yu Lin; Zhi Hu; Yu Zheng; Jose Hobson; De-Yi Wang (Chemical Engineering Journal, 2023)

The genomes of medicinal skullcaps reveal the polyphyletic origins of clerodane diterpene biosynthesis in the family Lamiaceae - Haixiu Li; Song Wu; Ruoxi Lin; Yiren Xiao; Ana Luisa Malaco Morotti; Ya Wang; Meytal Galilee; Haowen Qin; Tao Huang; Yong Zhao; Xun Zhou; Jun Yang; et al. (Molecular Plant, 2023)

Neogene subduction initiation models in the western Pacific and analysis of subduction zone parameters - Min Li; Song Huang; Tianyao Hao; Miao Dong; Ya Xu; Jian Zhang; Qingyu He; Gui Fang (Science China Earth Sciences, 2023)

Hydraulic determinants of drought-induced tree mortality and changes in tree abundance between two tropical forests with different water availability - Yong-Qiang Wang; Hui-Qing Song; Ya-Jun Chen; Pei-Li Fu; Jiao-Lin Zhang; Kun-Fang Cao; Shi-Dan Zhu (Agricultural and Forest Meteorology, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

Alternations of interhemispheric functional connectivity in patients with optic neuritis using voxel-mirrored homotopic connectivity: A resting state fMRI study - Ke Song; Ya-Li Lv; Li-juan Yang; Peng Lv; Bo Ren; Jun Tian; Dao-qing Wei; Huan Li; Yi Shao (Brain Imaging and Behavior, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

The oxidative damage of the Lagerstroemia indica chlorosis mutant gl1 involves in ferroptosis - Sumei Li; Shuan Wang; Zhenxing Song; Peng Wang; Fenni Lv; Rutong Yang; Ya Li (Journal of Plant Physiology, 2023)

Sedimentary dinoflagellate cyst records of human-induced environmental changes in Daya Bay, the northern South China Sea - Ping-Ping Shen; Ying Li; Ya-Nan Tang; Qing-Shang Song; Yue Xue (Journal of Marine Systems, 2023)

Association between ambient carbon monoxide levels and hospitalization costs of patients with myocardial infarction: Potential effect modification by ABO blood group - Qing-Song Huang; Lai-Xin Zhou; Li-Li Yang; Yue-Xu Jiang; Hua Xiao; Da-Wei Li; Yu-Meng Zhou; Yue-Gu Hu; Na Li; Ya-Fei Li; Ai-Ling Ji; Peng Luo; et al. (Environmental Research, 2023)

Biochemical, transcriptomic and metabolomic responses to total dissolved gas supersaturation and their underlying molecular mechanisms in Yangtze sturgeon (Acipenser dabryanus) - Yeyu Chen; Xiaoyun Wu; Xiaoqing Liu; Jiansheng Lai; Ya Liu; Mingjiang Song; Feiyang Li; Quan Gong (Environmental Research, 2023)

Heteroaggregation effects on Pickering stabilization using oppositely charged cellulose nanocrystal and nanochitin - Shasha Guo; Ya Zhu; Wenyang Xu; Siqi Huan; Jun Li; Tao Song; Long Bai; Orlando J. Rojas (Carbohydrate Polymers, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Association between gestational arsenic exposure and intrauterine growth restriction: the role of folate content - Fei-Xiang Xu; Xu Chen; Heng Zhang; Yi-Jun Fan; Ya-Ping Song; Jin-Wei Lv; Ya-Li Xie; Yichao Huang; Dao-Zhen Chen; Hua Wang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

The association between short-term ambient sulfur dioxide exposure and hospitalization costs of ischemic stroke: a hospital-based study in Chongqing, China - En-Jie Tang; Yu-Meng Zhou; Li-Li Yang; Nan Wang; Yue-Xu Jiang; Hua Xiao; Yue-Gu Hu; Da-Wei Li; Na Li; Qing-Song Huang; Ning Du; Ya-Fei Li; et al. (Environmental Science and Pollution Research, 2022)

Experimental study on the characteristics of slag-lime-water glass composite cured mud - Jin-Song Zhang; Ya-Xing Wang; Jian-Yong Pang; Xu Li (Arabian Journal of Geosciences, 2022)

Study on reflection and transmission characteristics of shear waves at sediment layer interface - Pan Ji-Shun; Song Chao-Yang; Li Chang-Zheng; Liu Ya-Li (Applied Geophysics, 2022)

Overexpression of the PLK4 Gene as a Novel Strategy for the Treatment of Autosomal Recessive Microcephaly by Improving Centrosomal Dysfunction - Ya-Song Xu; Zhi-Ying Su; Li Sun; Xiao-Mei Yang; Shi-Yu Sun; Xiao-Fei Ji; Yi-Zhen Ji; Su-Qing Zhang; Jie Tian; Qi-Chang Wu (Journal of Molecular Neuroscience, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Dynamic characteristics and drivers of the regional household energy-carbon-water nexus in China - Hao Li; Yuhuan Zhao; Lu Zheng; Song Wang; Jianing Kang; Ya Liu; Hongxian Li; Long Shi; Yuli Shan (Environmental Science and Pollution Research, 2021)

24-epibrassinolide improves differential cadmium tolerance of mung bean roots, stems, and leaves via amending antioxidative systems similar to that of abscisic acid - Ya-Juan Song; Yi Li; Yan Leng; Shi-Weng Li (Environmental Science and Pollution Research, 2021)

Interaction of magnolia bark extracts with Staphylococcus aureus DNA and evaluation of the stability of their antibacterial activities - Shu-Mei Cui; Hai-yun Liang; Ting Li; Ke-Ke He; Yu-Mei Zheng; Meng Tang; Chong-rong Ke; Li-Ya Song (Archives of Microbiology, 2021)

On the origin of SARS-CoV-2—The blind watchmaker argument - Chung-I Wu; Haijun Wen; Jian Lu; Xiao-dong Su; Alice C. Hughes; Weiwei Zhai; Chen Chen; Hua Chen; Mingkun Li; Shuhui Song; Zhaohui Qian; Qihui Wang; et al. (Science China Life Sciences, 2021)

Prediction of marine heat flow based on the random forest method and geological and geophysical features - Min Li; Song Huang; Miao Dong; Ya Xu; Tianyao Hao; Xueshan Wu; Yufeng Deng (Marine Geophysical Research, 2021)

p -Terphenyls and actinomycins from a Streptomyces sp. associated with the larva of mud dauber wasp - Dan-Dan Lu; Jin-Wei Ren; Qian-Qian Du; Ya-Jie Song; Shi-Qi Lin; Xia Li; Er-Wei Li; Wei-Dong Xie (Natural Product Research, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Influence of the roots of mixed-planting species on the shear strength of saline loess soil - Ya-bin Liu; Xia-song Hu; Dong-mei Yu; Hai-li Zhu; Guo-rong Li (Journal of Mountain Science, 2021)

Retraction Note to: NPC-16, a novel naphthalimide–polyamine conjugate, induced apoptosis and autophagy in human hepatoma HepG2 cells and Bel-7402 cells - Song-qiang Xie; Qian Li; Ya-hong Zhang; Jian-hong Wang; Zi-hou Mei; Jin Zhao; Chao-jie Wang (Apoptosis, 2021)

Correction to: The effect of teprenone on the intestinal morphology and microbial community of Chinese sea bass (Lateolabrax maculatus) under intermittent hypoxic stress - Hong-biao Dong; Yong-xu Sun; Ya-fei Duan; Hua Li; Yong Li; Qing-song Liu; Wen-hao Wang; Jia-song Zhang (Fish Physiology and Biochemistry, 2020)

Greater promotion of DNRA rates and nrfA gene transcriptional activity by straw incorporation in alkaline than in acidic paddy soils - Ren Bai; Yun-Ting Fang; Liu-Ying Mo; Ju-Pei Shen; Lin-Lin Song; Ya-Qi Wang; Li-Mei Zhang; Ji-Zheng He (Soil Ecology Letters, 2020)

Highly sensitive serological approaches for Pepino mosaic virus detection - Wan-qin He; Jia-yu Wu; Yi-yi Ren; Xue-ping Zhou; Song-bai Zhang; Ya-juan Qian; Fang-fang Li; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2020)

The effect of teprenone on the intestinal morphology and microbial community of Chinese sea bass (Lateolabrax maculatus) under intermittent hypoxic stress - Hong-biao Dong; Yong-xu Sun; Ya-fei Duan; Hua Li; Yong Li; Qing-song Liu; Wen-hao Wang; Jia-song Zhang (Fish Physiology and Biochemistry, 2020)

Retrospective analysis of HIV-1 drug resistance mutations in Suzhou, China from 2009 to 2014 - Yanhui Song; Jingping Hu; Jun He; Chunsheng Dong; Ying Yuan; Yuan Li; Ronghua Li; Xuerong Ya (Virus Genes, 2020)

Characterization, tissue distribution of resistin gene and the effect of fasting and refeeding on resistin mRNA expression in Siberian sturgeon ( Acipenser baerii ) - Ni Tang; Yanlin Liu; Zhengzhi Tian; Shaoqi Xu; Mei Wang; Hu Chen; Bin Wang; Ya Li; Yan Wang; Song Yang; Liulan Zhao; Defang Chen; et al. (Journal of Fish Biology, 2020)
Resistin as an adipokine identified from rodents in 2001 is involved in many biological processes. However, little is known about this gene in fish. We cloned Siberian sturgeon ( Acipenser baerii ) resistin cDNA of 795 base pairs, encoding 107 amino acids, which showed 38–40% identity to human and rodents. Real‐time quantitative PCR showed that the resistin gene was widely distributed in tissues of Siberian sturgeon, with the highest expression in liver. After fasting for 1, 3, 6 and 10 days, the expression of the resistin gene in the liver of Siberian sturgeon decreased significantly, and after refeeding on the 10 days of fasting the resistin mRNA expression increased rapidly, suggesting that resistin may play an important role in liver in response to starvation. Taken together, these results suggest that resistin may be involved in the regulation of energy homeostasis in liver.

Antibacterial Effects of Schisandra chinensis Extract on Escherichia coli and its Applications in Cosmetic - S. Mei Cui; T. Li; Q. Wang; K. Ke He; Y. Mei Zheng; H. Yun Liang; L. Ya Song (Current Microbiology, 2020)

cDNA-AFLP analysis of differentially expressed genes during microspore embryogenesis in non-heading Chinese cabbage - Ya Zhang; Su-yan Gao; Huan-huan Liu; Xi-lin Zhang; Ai-song Zeng; Jian-jun Wang; Xi-lin Hou; Ying Li (In Vitro Cellular & Developmental Biology - Plant, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Complete genome sequences of five prunus necrotic ringspot virus isolates from Inner Mongolia of China and comparison to other PNRSV isolates around the world - Shuang Song; Ping-ping Sun; Ya-han Chen; Qiang Ma; Xiao-yun Wang; Ming-min Zhao; Zheng-nan Li (Journal of Plant Pathology, 2019)

High genetic diversity and recombination events of porcine astrovirus strains identified from ill and asymptomatic pigs in 2017, Hunan Province, China - Sun-Liang Lv; Hui-Hui Zhang; Jie-Yu Li; Wen-Qin Hu; Ya-Ting Song; Tanja Opriessnig; Chao-Ting Xiao (Virus Genes, 2019)

Scenario analysis of ETS revenue allocation mechanism of China: based on a dynamic CGE model - Hao Li; Yuhuan Zhao; Song Wang; Jiang Lin; Ye Cao; Qiaoling Shi; Ya Liu; Yanli Xiao; Junjie Li (Environmental Science and Pollution Research, 2019)

Spatial variation and soil nitrogen potential hotspots in a mixed land cover catchment on the Chinese Loess Plateau - Yun-long Yu; Zhao Jin; Henry Lin; Yun-qiang Wang; Ya-li Zhao; Guang-chen Chu; Jing Zhang; Yi Song; Han Zheng (Journal of Mountain Science, 2019)

Influences of soil moisture and salt content on loess shear strength in the Xining Basin, northeastern Qinghai-Tibet Plateau - Jiang-tao Fu; Xia-song Hu; Xi-lai Li; Dong-mei Yu; Ya-bin Liu; You-Qing Yang; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2019)

Functions of RNA N6-methyladenosine modification in cancer progression - Bing Chen; Ya Li; Ruifeng Song; Chen Xue; Feng Xu (Molecular Biology Reports, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Pond-bottom decomposition of leaf litters canopied by free-floating vegetation - Ya-Lin Zhang; Hong-Bin Li; Li Xu; Xu Pan; Wen-Bing Li; Jian Liu; Yue-Ping Jiang; Yao-Bin Song; Ming Dong (Environmental Science and Pollution Research, 2019)

Long noncoding RNA UCA1 promotes the proliferation of hypoxic human pulmonary artery smooth muscle cells - Tian-Tian Zhu; Rui-Li Sun; Ya-Ling Yin; Jin-Ping Quan; Ping Song; Jian Xu; Ming-Xiang Zhang; Peng Li (Pflügers Archiv - European Journal of Physiology, 2019)

Functions of RNA N6-methyladenosine modification in cancer progression - Bing Chen; Ya Li; Ruifeng Song; Chen Xue; Feng Xu (Molecular Biology Reports, 2019)

Sesquiterpenes and lignans from the flower buds of Daphne genkwa and their nitric oxide inhibitory activities - Chun-Yang Zhang; Lan Luo; Jing Xia; Ya-Nan Song; Li-Jun Zhang; Miao Zhang; Khalid Rahman; Yin Ye; Hong Zhang; Jian-Yong Zhu (Natural Product Research, 2018)

Occurrence of Telenomus dignus (Gahan) on the Sugarcane Borers, Scirpophaga intacta Snellen and Chilo sacchariphagus Bojer in Guangxi Province, China - Zhen-Qiang Qin; François-Régis Goebel; De-Wei Li; Jin-Ju Wei; Xiu-Peng Song; Ya-Wei Luo; Lu Liu; Zhan-Yun Deng (Sugar Tech, 2018)

Three new 3,4-seco-cycloartane triterpenes from Gardenia sootepensis - Wei-Wu Song; Xue-Qin Wang; Hua-Li Jia; Zheng-Kun Zhang; Yong-Jie Ding; Ya-Hong Chen (Natural Product Research, 2018)

Preparation and application of magnetic nitrogen-doped rGO for persulfate activation - Ya Pang; Kun Luo; Lin Tang; Xue Li; Yong Song; Cheng-yong Li; Li-ping Wang (Environmental Science and Pollution Research, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Variable hydrological effects of herbs and shrubs in the arid northeastern Qinghai-Tibet Plateau, China - Ya-bin Liu; Ying Zhang; Jiang-tao Fu; Dong-mei Yu; Xia-song Hu; Xi-lai Li; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2018)

Association of Interleukin-17F gene polymorphisms with susceptibility to severe enterovirus 71 infection in Chinese children - Fei Li; Peipei Liu; Ya Guo; Zhenliang Han; Yedan Liu; Yuanyuan Wang; Long Song; Jianguo Cheng; Zongbo Chen (Archives of Virology, 2018)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Heterogeneous expression of the cotton R2R3-MYB transcription factor GbMYB60 increases salt sensitivity in transgenic Arabidopsis - Fu-Chun Xu; Hui-Li Liu; Yun-Yun Xu; Jing-Ruo Zhao; Ya-Wei Guo; Lu Long; Wei Gao; Chun-Peng Song (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Establishment and characterization of a kidney cell line from kelp grouper Epinephelus moara - Xiao-Feng Liu; Ya-Hong Wu; Shi-Na Wei; Na Wang; Peng-Fei Li; Yang-Zhen Li; Nian-Wei Zhang; Qi-Wei Qin; Song-Lin Chen (Fish Physiology and Biochemistry, 2018)

Impact of IL-10-1082A/G gene polymorphism on the severity of EV71 infection in Chinese children - Qiubo Li; Hongfang He; Ya Guo; Yu Zhang; Peipei Liu; Yedan Liu; Chengqing Yang; Jie Song; Na Zhang; Zongbo Chen (Archives of Virology, 2018)

The relationship of chromophoric dissolved organic matter parallel factor analysis fluorescence and polycyclic aromatic hydrocarbons in natural surface waters - Sijia Li; Ya’nan Chen; Jiquan Zhang; Kaishan Song; Guangyi Mu; Caiyun Sun; Hanyu Ju; Meichen Ji (Environmental Science and Pollution Research, 2018)

Comprehensive Benefit Evaluation System for Low-Impact Development of Urban Stormwater Management Measures - Jiake Li; Chenning Deng; Ya Li; Yajiao Li; Jinxi Song (Water Resources Management, 2017)

Two new phenolic glycosides from the stem of Zanthoxylum armatum DC - Tao Guo; Li-Ping Dai; Xiao-Feng Tang; Tong-Tong Song; Ya Wang; Ai-Hong Zhao; Ying-Ying Cao; Jun Chang (Natural Product Research, 2017)

RETRACTED ARTICLE: Autophagy regulated by lncRNA HOTAIR contributes to the cisplatin-induced resistance in endometrial cancer cells - Meng-Yao Sun; Jian-Yong Zhu; Chun-Yan Zhang; Miao Zhang; Ya-Nan Song; Khalid Rahman; Li-Jun Zhang; Hong Zhang (Biotechnology Letters, 2017)

Fasudil Enhances Therapeutic Efficacy of Neural Stem Cells in the Mouse Model of MPTP-Induced Parkinson’s Disease - Yan-Hua Li; Jing-Wen Yu; Jian-Yin Xi; Wen-Bo Yu; Jian-Chun Liu; Qing Wang; Li-Juan Song; Ling Feng; Ya-Ping Yan; Guang-Xian Zhang; Bao-Guo Xiao; Cun-gen Ma (Molecular Neurobiology, 2017)

Molecular identification of differential expression genes associated with sex pheromone biosynthesis in Spodoptera exigua - Ya-Nan Zhang; Long-Wa Zhang; Da-Song Chen; Liang Sun; Zhao-Qun Li; Zhan-Feng Ye; Mei-Yan Zheng; Jin-Bu Li; Xiu-Yun Zhu (Molecular Genetics and Genomics, 2017)

Downregulation of miR-221-3p contributes to IL-1β-induced cartilage degradation by directly targeting the SDF1/CXCR4 signaling pathway - Xin Zheng; Feng-chao Zhao; Yong Pang; Dong-ya Li; Sheng-cheng Yao; Shao-song Sun; Kai-jin Guo (Journal of Molecular Medicine, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

High genetic diversity and absence of phylogeographic structure in breeding populations of vulnerable Saundersilarus saundersi (Charadriiformes: Laridae) in Bohai Bay, China - Ya-Nan Zhang; Bo-Ye Liu; Lu Dong; Hong-Xing Jiang; Xuan Wang; Xue-Min Wang; Chang-Zhan Song; Xiu-Ming Li; Shu-Hong Li (Conservation Genetics, 2017)

Decomposition and scenario analysis of CO2 emissions in China’s power industry: based on LMDI method - Yuhuan Zhao; Hao Li; Zhonghua Zhang; Yongfeng Zhang; Song Wang; Ya Liu (Natural Hazards, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Synergistic and Superimposed Effect of Bone Marrow-Derived Mesenchymal Stem Cells Combined with Fasudil in Experimental Autoimmune Encephalomyelitis - Jing-Wen Yu; Yan-Hua Li; Guo-Bin Song; Jie-Zhong Yu; Chun-Yun Liu; Jian-Chun Liu; Hai-Fei Zhang; Wan-Fang Yang; Qing Wang; Ya-Ping Yan; Bao-Guo Xiao; Cun-Gen Ma (Journal of Molecular Neuroscience, 2016)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

A new phenolic derivative with soluble epoxide hydrolase and nuclear factor-kappaB inhibitory activity from the aqueous extract of Acacia catechu - Ya Nan Sun; Wei Li; Seok Bean Song; Xi Tao Yan; Yan Zhao; A. Reum Jo; Jong Seong Kang; Kim Young Ho (Natural Product Research, 2016)

Arctigenin Confers Neuroprotection Against Mechanical Trauma Injury in Human Neuroblastoma SH-SY5Y Cells by Regulating miRNA-16 and miRNA-199a Expression to Alleviate Inflammation - Jie Song; Na Li; Yang Xia; Zhong Gao; Sa-Feng Zou; Yu-Hui Yan; Shao-Heng Li; Yue Wang; Ya-Kun Meng; Jing-Xian Yang; Ting-Guo Kang (Journal of Molecular Neuroscience, 2016)

Quantitative determination constraints on dolomitization model for the Upper Permian Changxing reservoir dolomites of Northeastern Sichuan Basin, Southwestern China - Rui Zhao; Ya Sheng Wu; Hong Xia Jiang; Qing Song Liu; Li Jing Liu (Carbonates and Evaporites, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Statistical culture-based strategies to enhance chlamydospore production by Trichoderma harzianum SH2303 in liquid fermentation - Ya-qian Li; Kai Song; Ya-chai Li; Jie Chen (Journal of Zhejiang University-SCIENCE B, 2016)

JA, a new type of polyunsaturated fatty acid isolated from Juglans mandshurica Maxim, limits the survival and induces apoptosis of heptocarcinoma cells - Xiu-Li Gao; Hua Lin; Wei Zhao; Ya-Qin Hou; Yong-Li Bao; Zhen-Bo Song; Lu-Guo Sun; Shang-Yi Tian; Biao Liu; Yu-Xin Li (Apoptosis, 2016)

Association between occupational stressors and type 2 diabetes among Chinese police officers: a 4-year follow-up study in Tianjin, China - Hao Yu; Jin-chuan Liu; Ya-jiao Fan; Chen Li; Li-xin Zhang; Xi Chen; Song Yue; Wen-li Lu; Xi-lin Yang; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2016)

Culture temperature modulates monoclonal antibody charge variation distribution in Chinese hamster ovary cell cultures - Xintao Zhang; Ya-Ting Sun; Hongping Tang; Li Fan; Dongdong Hu; Jintao Liu; Xuping Liu; Wen-Song Tan (Biotechnology Letters, 2015)

Salt tolerance and alterations in cytosine methylation in the interspecific hybrids of Fraxinus velutina and Fraxinus mandshurica - Fan-Suo Zeng; Lei-Lei Li; Nan-Song Liang; Xuan Wang; Xiang Li; Ya-Guang Zhan (Euphytica, 2015)

P5-2 of rice black-streaked dwarf virus is a non-structural protein targeted to chloroplasts - Xiao-Ya Liu; Jian Yang; Li Xie; Jing Li; Xi-Jiao Song; Jian-Ping Chen; Heng-Mu Zhang (Archives of Virology, 2015)

Prognostic Factors of Survival in Pathologic Incomplete Response Patients with Locally Advanced Breast Cancer After Neoadjuvant Chemotherapy - Ou Huang; Min Jiang; Xiao-song Chen; Jia-yi Wu; Wei-guo Chen; Ya-fei Li; Kun-wei Shen (Cell Biochemistry and Biophysics, 2015)

Rooting characteristics of two widely distributed woody plant species growing in different karst habitats of southwest China - Yun-peng Nie; Hong-song Chen; Ke-lin Wang; Ya-li Ding (Plant Ecology, 2014)

Seasonal variations in leaf δ13C values: implications for different water-use strategies among species growing on continuous dolomite outcrops in subtropical China - Yun-peng Nie; Hong-song Chen; Ke-lin Wang; Ya-li Ding (Acta Physiologiae Plantarum, 2014)

Correlation of the UGT1A4 gene polymorphism with serum concentration and therapeutic efficacy of lamotrigine in Han Chinese of Northern China - Ying Chang; Li-ya Yang; Meng-chao Zhang; Song-Yan Liu (European Journal of Clinical Pharmacology, 2014)

17β-Estradiol protects against apoptosis induced by levofloxacin in rat nucleus pulposus cells by upregulating integrin α2β1 - Si-Dong Yang; Lei Ma; Ti-Xin Gu; Wen-Yuan Ding; Feng Zhang; Yong Shen; Ying-Ze Zhang; Da-Long Yang; Di Zhang; Ya-Peng Sun; Yan-Li Song (Apoptosis, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Ovalbumin enhances YKL-40, IL-5, GM-CSF, and eotaxin expression simultaneously in primarily cultured mouse tracheal epithelial cells - Su-qin Ben; Ya-li Qiu; Juan Zhou; Xiao-yu Zhou; Shan Zhang; Yi Wu; Shao-qing Ju; Song-shi Ni (In Vitro Cellular & Developmental Biology - Animal, 2014)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

Association of 10q23 with colorectal cancer in a Chinese population - Fen-Xia Li; Xue-Xi Yang; Xuan-Qiu He; Ni-Ya Hu; Ying-Song Wu; Ming Li (Molecular Biology Reports, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Choline inhibits angiotensin II-induced cardiac hypertrophy by intracellular calcium signal and p38 MAPK pathway - Shu Wang; Hong-mei Han; Zhen-wei Pan; Peng-zhou Hang; Li-hua Sun; Ya-nan Jiang; Hao-xin Song; Zhi-min Du; Yan Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

3-Nitro-naphthalimide and nitrogen mustard conjugate NNM-25 induces hepatocellular carcinoma apoptosis via PARP-1/p53 pathway - Song-qiang Xie; Ya-hong Zhang; Qian Li; Feng-hua Xu; Jiu-wang Miao; Jin Zhao; Chao-jie Wang (Apoptosis, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

Analysis of Lanthanide-Induced Conformational Change of the C-Terminal Domain on Centrin - Ya-Qin Zhao; Jun Yan; Li Song; Ya-Nan Feng; Ai-Hua Liang; Bin-Sheng Yang (Journal of Fluorescence, 2012)

Mesozoic collision-related magmatism and crust–mantle interaction along the Anhui segment of the Yangtze River Valley, east-central China - Da-Peng Li; Yang-Song Du; Ya-Fei Wang; Xin Lu; Yi Cao (International Geology Review, 2011)

RETRACTED ARTICLE: NPC-16, a novel naphthalimide–polyamine conjugate, induced apoptosis and autophagy in human hepatoma HepG2 cells and Bel-7402 cells - Song-qiang Xie; Qian Li; Ya-hong Zhang; Jian-hong Wang; Zi-hou Mei; Jin Zhao; Chao-jie Wang (Apoptosis, 2011)

TiO2-Assisted Photodegradation of Direct Blue 78 in Aqueous Solution in Sunlight - Ya-Li Song; Ji-Tai Li; Bo Bai (Water, Air, & Soil Pollution, 2010)

Dynamic behavior of glycerol–glucose co-fermentation for 1,3-propanediol production by Klebsiella pneumoniae DSM 2026 under micro-aerobic conditions - Li-Hui Sun; Zhi-Yuan Song; Ya-Qin Sun; Zhi-Long Xiu (World Journal of Microbiology and Biotechnology, 2010)

Ectopic overexpression of AtHDG11 in tall fescue resulted in enhanced tolerance to drought and salt stress - Ya-Jun Cao; Qiang Wei; Yang Liao; He-Ling Song; Xian Li; Cheng-Bin Xiang; Ben-Ke Kuai (Plant Cell Reports, 2009)

Intestinal microflora in rats with ischemia/reperfusion liver injury - Hui-chun Xing; Lan-juan Li; Kai-jin Xu; Tian Shen; Yun-bo Chen; Ji-fang Sheng; Yun-song Yu; Ya-gang Chen (Journal of Zhejiang University-SCIENCE B, 2005)

Selection of biochemical mutants of Aspergillus niger with enhanced extracellular ribonuclease production - Ya-Hong Xiong; Jian-Zhong Liu; Hai-Yan Song; Li-Ping Weng; Liang-Nian Ji (World Journal of Microbiology and Biotechnology, 2004)